Characterization of potassic alteration in the Iju porphyry copper deposit using mineral chemistry of biotite and chlorite - Alireza Zarasvandi (Petrology, 2018)
The Iju porphyry copper deposit is located 72 km NE of Shahr-e- Babak in the western part of the Dehaj - Sardueih zone in the Kerman Cenozoic volcano - plutonic belt. In this deposit, the Miocene granitoids with dominant composition of granite, granodiorite, tonalite and quartz diorite were intruded in the Eocene volcanic and pyroclastic sequences. The potassic, propylitic, potassic-phyllic, phyllic and argillic facies are the main hydrothermal alterations in the Iju intrusive masses. Nevertheless, the hypogene mineralization is manly occurred in the potassic alteration. The aim of present work is the investigation of reequilibrated biotite and chlorite chemistry to characterize the potassic alteration in the onset of mineralization. Also, the chlorite data is used for assessing the geochemical changes owing to chloritization of biotite. Based on reequilibrated biotites, it is proved that oxygen fugacity during the potassic alteration was high so that mostly belongs to the hematite- magnetite buffering district. Moreover, the temperature in the onset of sulphide mineralization has an average of 399.85 °C. According to variations in Log (fH2O/fHF) and Log (fH2O/fHCl) values, it seems that non-homogenous hydrothermal fluids were contributed in the formation of potassic alteration in the Iju deposit. Secondary chlorites that replaced biotite have clinochlore composition and chloritization occurred around 325.48 to 373.51 °C. The chloritization process lead to Mg increasing as well as significant K2O and SiO2 decreasing contents due to the formation of K-feldspar minerals. Overall, it seems that high temperatures and the prevailing of high oxygen fugacity could be considered as one of main reasons for the low sulphide mineralization and the sub-economic nature of the Iju porphyry deposit.